Intracardiac Metastasis from a Large Cell Neuroendocrine Lung Carcinoma - Gaisendrees, Christopher; Eghbalzadeh, Kaveh; Mader, Navid; Wahlers, Thorsten C. W. (The Thoracic and Cardiovascular Surgeon Reports, 2019)
Primary malignant tumors of the heart are rare; the biggest group is sarcomas. Cardiac metastases make up the biggest group of secondary cardiac tumors. We present a rare case of cardiac metastasis (3.1 × 3.2 × 2.8 cm) localized in the right atrium, originating from a large cell neuroendocrine lung carcinoma, with close contact to the tricuspid valve and inferior cava vein.
Keywords: cardiac tumor; cardiovascular; surgery; metastases; lung cancer; heart; tricuspid valve